Pelatihan Pembacaan Kitab-Kitab Sholawat untuk Kegiatan Safari Maulid Al-Arba’in Majelis Ilmu dan Amal (Mia) Al-Burdah Baa Khaalish 2002 Bagi Masyarakat Pulau Bengkalis - Wira Sugiarto; Riki Astafi (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Training Activity of Reading Sholawat Books for Safari Maulid Al-Arba'in Majelis Ilmu dan Amal (MIA) Al-Burdah Baa Khalish 2002 held on Bengkalis Island aims to improve the community's understanding of reading sholawat, deepen spirituality, and strengthen social ties among local Muslims. This training involves various methods, including lectures, presentations, group discussions, and repeated exercises, which are adjusted to local cultural needs. In addition to improving the technique of reading and experiencing sholawat, this activity also functions as a means of preserving Malay cultural traditions, such as rebana and gambus music, which often accompany the reading of sholawat in society. In addition, this training also has a positive impact in strengthening ukhuwah Islamiyah (brotherhood) between community members, and involving the younger generation in preserving religious and cultural traditions. The results of this community service show that through an approach that unites local religion and culture, religious activities like this can enrich the spiritual experience of the community, while strengthening their religious and cultural identity. If there is a desire and further development, it is recommended to involve digital technology, expand community participation, and increase the involvement of the younger generation in every existing religious activity.